2016
DOI: 10.18844/gjit.v6i1.394
|View full text |Cite
|
Sign up to set email alerts
|

The effects of problem based learning on cognitive flexibility, self-regulation skills and students’ achievements

Abstract: The purpose of this study is to specify the effects of cognitive flexibility and self-regulation skills on students’ achievements in web mediated problem based programming language learning towards gender and class groups. Self-regulation skills towards web based programming language education is discussed under three dimensions; learning skills, learning strategies and self-efficacy. Level of cognitive flexibility is reviewed by comparison of time and percentage of success. Causal-comparative research model i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 0 publications
0
10
0
3
Order By: Relevance
“…It is thought that teachers who face dozens of undesirable behaviours in the classroom each day are important in learning more about the prevention of the unwanted behaviour related to the problem-solving skills of teachers and the quality management of the learning-teaching process. Research has emphasized that the level of cognitive flexibility and problem solving skills are interrelated (Canas, Quesada, Antolí, & Fajardo, 2003;Isen, 1999;Fitzgerald, 1997;Krems, 1995;Walker, Liston, Hobson, & Stickgold, 2002;Yucel, 2011). In this research, it was understood that pre-service teachers have a weak positive relationship between their cognitive flexibility skills and their interpersonal problem solving skills.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 92%
“…It is thought that teachers who face dozens of undesirable behaviours in the classroom each day are important in learning more about the prevention of the unwanted behaviour related to the problem-solving skills of teachers and the quality management of the learning-teaching process. Research has emphasized that the level of cognitive flexibility and problem solving skills are interrelated (Canas, Quesada, Antolí, & Fajardo, 2003;Isen, 1999;Fitzgerald, 1997;Krems, 1995;Walker, Liston, Hobson, & Stickgold, 2002;Yucel, 2011). In this research, it was understood that pre-service teachers have a weak positive relationship between their cognitive flexibility skills and their interpersonal problem solving skills.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 92%
“…There was a significant correlation between CF scores and success in examinations, and the students with a high level of CF were found to be more successful. Yucel, Karahoca and Karahoca (2015) also found in their study a positive linear correlation between CF and student achievement. It can be commented that students with higher level of CF are more successful.…”
Section: Discussionmentioning
confidence: 62%
“…It was found in the study of Alper and Deryakulu (2008) that the variable CF did not produce any significant difference in students' achievement, attitudes or permanence of learning. In the study of Yucel (2011), however, a positive linear correlation was found between student achievement and CF. There was a significant correlation between CF scores and success in examinations, and the students with a high level of CF were found to be more successful.…”
Section: Discussionmentioning
confidence: 78%
“…Bilişsel esneklik ile ilgili çalışmalarda alternatif bireyin zor durumlara karşı ürettiği yeni çözüm yolları olarak tanımlanmaktadır (Batting, 1979;Sapmaz, ve Doğan, 2013;Spiro, Feltovich, Jacobson, ve Coulson, 1991). Araştırmalar etkili alternatif üretebilmenin problem çözme becerisinin gelişimi ile ilgili olduğunu ortaya koymaktadır (Canas, Quesada, Antolí, ve Fajardo, 2003;Esen-Aygün, 2018;Fitzgerald, 1997;Isen, 2002;Krems, 1995;Yücel, 2011 (Armbruster, 1989;Deak, 2003;Schraw, 1998;Şendağ ve Odabaşı, 2009). Bu nedenle, bilişsel olarak koçluk yapma sorumluluğunu üstlenen öğretmenlerin (Demir ve Doğanay, 2010)…”
Section: Tartışma Ve öNerilerunclassified